Variability of the critical frequency of the f2 layer, fof2 in west africa using ionosonde stations at ouagadougou and dakar (2012)
The critical frequency of the F2 layer of the ionosphere, foF2 is responsible for various effects on radio communication such as refraction, scintillation, absorption, error in Global Positioning System (GPS), jitter and phase delay. The variations of the critical frequency of the F2 layer at two different locations over West Africa were studied using ionosonde data for a solar cycle (1979 to 1989) at low, moderate and high solar activity, 1986, 1983 and 1989, respectively. The ionosonde stations are Dakar in Senegal (15°N, 17°W) and Ouagadougou in Burkina Faso (12°N, 1,8°W). The investigation of critical frequency of the F2 layer, foF2 using Relative Standard Deviation (RSD) revealed the spread and the occurrence of foF2. The results obtained in this study are proposed as equatorial input values for the development of a Variability Model for the International Reference Ionosphere.